A Theoretical Framework And Principles For The Establishment Aand Management Of Civil Society Organizations In Vietnam - Nguyễn Mạnh Cường; Nguyễn Mạnh Cường (2008)
This guidebook was prepared to respond to the needs of civil society development in Vietnam. Along with the economic renovation process, democratic governance and social harmonization in Vietnam have motivated the active participation of civil society organizations in the development of public services and the participation in the consultation to assess the development policies.